Improvement of Interoceptive Processes after an 8-Week Body Scan Intervention - Fischer, Dana; Messner, Matthias; Pollatos, Olga (Frontiers in Human Neuroscience, 2017)
Interoceptive processes are defined as ability to detect sensations arising within the body. There is a growing body of research investigating ways of improving interoceptive processes. One promising approach increasing the attention to bodily sensations is the body scan (BS), a method stemming from mindfulness-based stress reduction. Research so far revealed only heterogenous findings of meditational practice and mindfulness-based stress reduction on interoceptive processes. Even more importantly, there is no study considering the effect of an 8-week BS intervention on interoceptive processes and the distinguishable subdomains of interoception. Therefore, the main objective of this research is to examine the effects of a BS intervention on different interoceptive subdomains over eight weeks of training in two different samples. In study 1, healthy participants executed a 20 minutes standardized audiotaped BS in the BS intervention group (n=25) each day over eight weeks. The control group (n=24) listened to an audio book for the same amount of time. In study 2, the BS group (n=18) was compared to an inactive control group (n=18). In both studies, three measurement points were realized and interoceptive accuracy (IAc) - using a heartbeat perception task - as well as interoceptive sensibility (IS) - using confidence ratings for the heartbeat perception task and the subscale `interoceptive awareness` of the Eating Disorder Inventory-2 (EDI-2) - were assessed. In study 1, we found, as a descriptive trend, IAc and confidence ratings to be increased irrespective of the condition. However, post-hoc analysis revealed a significant improvement of IAc between T1 and T3 in the BS intervention only. IS revealed to be unaffected by the interventions. In study 2, we observed a significant positive effect of the BS intervention on IAc and confidence ratings compared to the inactive controls. As in study 1, IS (EDI-2) was unaffected by the intervention. The results highlight the fact that interoception can be improved by long-term interventions focusing on bodily signals. Further studies might focus on clinical samples showing deficits in interoceptive processes and could use other bodily systems for measurement (e.g., respiratory signals) as well methods manipulating body ownership.